Comparative analysis of entrepreneurial orientation of Croatian and Sweden students - Najla Podrug; Ivona Vrdoljak Raguž; Melisa Dedić (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The purpose of this paper is to examine the comparison of entrepreneurial orientation of Croatian and Swedish students. Croatian students show significantly lower entrepreneurial intention than Swedish students, and positive attitudes are more frequent with Swedish students. Design/methodology/approach - The cross-cultural research strategy used in this study was a narrowsample strategy which is based on a survey questionnaire comparison of the similar subcultures in different countries. Findings - Croatian students show significantly lower entrepreneurial intention, while positive entrepreneurial attitudes are more frequent with Swedish students. Interestingly, Swedish students consider the entrepreneurial climate to be more evident in their schools. This finding is especially significant if one considers the significantly lower entrepreneurial education of Swedish than Croatian students. Research limitations/implications - Conclusions based on this research are tentative and require further comparison including representatives of other cultures and faculties. Another limitation is identified through additional option of changing intentions and other factors of entrepreneurial orientation, and therefore would longitudinal research of tracking changes of entrepreneurial orientation over the years of study, as well as after studies, along with exploring the reasons of changing them, be desirable. The size of the sample of respondents appears as another potential limitation. Originality/value - Confidence in their own entrepreneurial skills for Croatian students is dependent on the support of the environment, which is not the case with Swedish students whose confidence depends solely on how individually entrepreneurial they are.
Keywords: M16; 330; entrepreneurial orientation; Croatia; Sweden